Tenofovir induced lichenoid drug eruption - Mrinal Gupta (Thieme Medical and Scientific Publishers Pvt. Ltd., 2015)
Cutaneous adverse reactions are a common complication of anti-retroviral therapy. Tenofovir is a newer anti-retroviral drug belonging to the nucleotide reverse transcriptase inhibitor group. Systemic adverse effects like nausea, vomiting, diarrhea, hepatotoxicity and renal toxicity are common with tenofovir but cutaneous adverse effects are rare. Lichenoid drug eruptions are a common adverse effect seen with a large variety of drugs including antimalarials, antihypertensives, nonsteroidal anti-inflammatory drugs and diuretics. Lichenoid drug eruption is a rare cutaneous adverse effect of tenofovir with only a single case reported till date. Here, we report a case of tenofovir induced lichenoid drug eruption in a 54-year-old human immunodeficiency virus affected male who presented with generalized lichenoid eruption after 6 weeks of initiation of tenofovir and complete clearance on cessation of the drug.